Keratosis of the Larynx - Rajasudhakar R; Sundara Raju H (Journal of All India Institute of Speech and Hearing, 1970)
Laryngeal keratosis is a rare condition characterized by irregular areas of thickening and cornification of the laryngeal mucous membrane. Much controversy exists regarding its etiology, treatment and terminology. Some authors interchange the term ‘keratosis laryngis’ with that of ‘leukoplakia’ of the larynx. There are however, others who believe that these terms are not inter-related. This paper made an attempt to describe some of the characteristic features of the disease by describing a case report to emphasize the acoustic parameters of voice before and after the medication.